DIPLOMASI VIETNAM DALAM MENYIKAPI KEBIJAKAN ILLEGAL FISHING INDONESIA 2016-2021 - Ridho Maulana Susanto, (2023)
ABSTRACT Indonesia is the largest archipelagic country where the sea in Indonesia has a very wide area, and it has a lot of marine resources. However, of all this, this has become one of the many factors in the occurrence of illegal fishing. This lures fishermen from other countries to carry out illegal fishing which makes Indonesia feel very disadvantaged. Indonesia has difficulties in terms of arrests. As is well known, Indonesia and Vietnam on border issues are not completely clear. Indonesia cannot help but oppose IUU fishing and many of their policies and actions are welcomed by the international community, despite the controversial nature of the fishing vessels that are sometimes sunk in public. In this study the authors used a qualitative approach and descriptive research type. The author also uses the Theory of Maritime Diplomacy and the Concept of Illegal Fishing to help analyze this problem. The results of the study state that Vietnam and Indonesia work together in maritime affairs, and how does the Vietnamese state respond to illegal fishing policies made by Indonesia